INVENTARISASI SERANGGA PERTANAMAN PADI PASANG SURUT PADA SAAT SEBELUM TANAM DI KABUPATEN INDRAGIRI HILIR, RIAU - Zahlul Ikhsan (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2018)
The agricultural ecosystem has a diversity of habitats that vary greatly from simple to complex. Observing the diversity of insects in agricultural areas is important to support increased production. An insect inventory study of tidal rice crops has been conducted in Indragiri Hilir Regency. Objective of research was to obtain information about the types of insects in tidal rice plant ecosystems. This research was conducted using purposive random sampling. Collection of insects was done using pitfall trap, yellow pan trap, swing nets and malaise traps. Tidal rice plantation area of ​​Indragiri regency has 8 types of insect order obtained from 4 types of traps installed, ie insect order diptera, hymenoptera, hemiptera, orthoptera, coleoptera, lepidoptera, collembola and odonata. The highest insect population at the time before the rice planting period was occupied by insects of the order, followed by hymenoptera, hemiptera, orthoptera, coleoptera, lepidotera, and collembola respectively. Indragiri's downstream rice cultivation has high biodiversity potential and biological agents to be developed.